A novel spring-structured coaxial hierarchical SiO2@Co3O4 nanowire as a lithium-ion battery anode and its in situ real-time lithiation. (16th October 2019) - Han, Tianli; Ding, Yingyi; Chen, Yu; Cheng, Dong; Zhou, Ping; Liu, Jinyun
Abstract: High capacity and stable anodes are demanded since the current graphite-based anode does not meet the high-performance requirements of emerging Li-ion battery systems. Herein, we present a novel spring-shaped hierarchical SiO2 @Co3 O4 nanowire composite, which exhibits good Li-storage performance. The special structure is able to effectively accommodate the change in structure during charge–discharge, and the coaxial hierarchical morphology enables rapid Li + ion and electron transfer. The spring-shaped SiO2 @Co3 O4 anode exhibits a capacity of 770 mAh g −1, along with a high Coulombic efficiency of 99.8% after 400 cycles. A stable rate performance even after three rounds of measurements is also achievable. In addition, the real-time lithiation of the SiO2 @Co3 O4 composite is investigated through an in situ transmission electron microscopy technology, which demonstrates the stable structure of the spring-shaped SiO2 @Co3 O4 composite during the rapid lithiation process.